Privacy and New Technologies in the Spanish Penal Code - García-Magna, Débora (My University, 2019)
New technologies have become widespread in recent years, generating a change in the way people communicate. This implies the emergence of new risks related to the growing tendency to share personal information on social networks. The holder of data risks losing control over them, especially when information is published or communicated to a third party. The unauthorized diffusion of private material previously received from the owner (sexting) has been recently incorporated to the Spanish Criminal Code. These conducts can also lead to committing crimes of blackmail, pornography, harassment, etc., and there is a high risk for the victim to be subject to humiliation and threats, affecting his or her social reputation, and even leading to mental health problems. After addressing in the first place the evolution of the right to privacy from jurisprudence and supranational instruments point of view, this research has questioned the decision of the Spanish legislator to criminalize sexting. The central element lies in the fact that it is the owner of the private material who first reveals it. It is interesting to analyze whether this initial cession may constitute a limit to the protection of this right, on the understanding that someone who freely decides to share certain areas of his or her intimate life is accepting the risk that such sensitive information will come to the attention of third persons. The research has attended to the principles of criminal law, and has criticized the legislative technique used, as there are numerous aspects that the criminal type does not resolve. However, it was necessary to cover a punitive gap, so, therefore, the decision to criminalize these behaviors is considered appropriate. Of course there are many aspects that need improvement, and empirical studies must be carried out in order to assess the effects of this new regulation.
Keywords: Nuevas tecnología; Corte Europea de Derecho Humanos; Crimen - Legislación; New technologies; Criminal Law; European Court of Human Rights; Sexting